Oil and gas infrastructure decommissioning in marine protected areas: System complexity, analysis and challenges. (October 2018) - Burdon, D.; Barnard, S.; Boyes, S.J.; Elliott, M.
Abstract: Many offshore oil and gas production facilities are nearing the end of their operational life, with decommissioning now becoming a global challenge. The compatibility of decommissioning operations to marine protected areas (MPAs) creates further challenges. The recently-developed DAPSI(W)R(M) problem structuring framework (covering Drivers, Activities, Pressures, State changes, Impacts (on Welfare) and Responses (as Measures)) was applied here to interrogate the complexity of decommissioning oil and gas infrastructure within MPAs, with outputs feeding into the development of a novel database tool for Screening Potential Impacts of Decommissioning Activities (SPIDA). In meeting the current requirements of the marine regulatory regime, SPIDA provides a more streamlined, evidence-based process which can be applied by industry, statutory nature conservation bodies and regulators for identifying and evaluating evidence that supports the implications of decommissioning alternatives on the condition of MPAs. SPIDA has been developed to be adapted for other activities and sectors, including offshore renewables. Highlights: Decommissioning oil and gas infrastructure in marine protected areas is complex. A decision support framework was co-produced with key marine stakeholders. Novel tool was built for Screening Potential Impacts of Decommissioning Activities. SPIDA identifies risks, opportunities and impacts of decommissioning on features. The framework and tool are of relevance to other marine sectors e.g. offshore wind.